Tulip sees America - Rylant, Cynthia (Blue Sky Press, 1998)
Newbery Medalist Cynthia Rylant and award-winning illustrator Lisa Desimini celebrate the beauty of America. This vibrant, inspiring picture book captures a fun-filled drive across the country. A young man and his dog, Tulip, marvel at the farms in Iowa, the skies in Nebraska, the wind in Wyoming, and many more exquisite visions of America the beautiful. Full color